2020
DOI: 10.1088/1361-6595/ab8e4e
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of streamer-to-spark transitions in the first pulse and the post discharge stage

Abstract: The streamer-to-spark transition in a point-to-plane configuration in atmospheric pressure air is studied using a 2D–0D combined approach. A validated fluid code is used and improved to model the spark stage. 2D modeling of discharges at three different temperatures, 300, 600 and 800 K, are conducted; the spark transition occurs when the temperature reaches 800 K in the first pulse. A conservative criteria of spark transition temperature is proposed based on analytical solution and compared with experiments. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 59 publications
4
42
0
Order By: Relevance
“…Recently, several experimental and numerical studies in point-to-plane geometry in air gaps of about 1 cm at atmospheric pressure have reported images of axisymmetric diffuse discharges with maximum radius of several centimeters as reviewed in Naidis et al (2018) and shown since then in Brisset et al (2019); Chng et al (2019); Tarasenko et al (2020); Tarasenko (2020); Chen et al (2020); Bourdon et al (2020); Babaeva and Naidis (2021); Zhu et al (2021). These discharges are obtained using high voltage pulses (with maximum voltages being five or ten times higher than classical steady-state breakdown levels) applied with sub-nanosecond and nanosecond rise times.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several experimental and numerical studies in point-to-plane geometry in air gaps of about 1 cm at atmospheric pressure have reported images of axisymmetric diffuse discharges with maximum radius of several centimeters as reviewed in Naidis et al (2018) and shown since then in Brisset et al (2019); Chng et al (2019); Tarasenko et al (2020); Tarasenko (2020); Chen et al (2020); Bourdon et al (2020); Babaeva and Naidis (2021); Zhu et al (2021). These discharges are obtained using high voltage pulses (with maximum voltages being five or ten times higher than classical steady-state breakdown levels) applied with sub-nanosecond and nanosecond rise times.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the understanding of conditions in which a diffuse nanosecond positive ionization wave can be obtained in atmospheric pressure air is of particular interest. So far, the number of experimental and numerical studies on positive diffuse discharges in atmospheric pressure air remains limited (Naidis et al, 2018;Tardiveau et al, 2009;Pechereau et al, 2014;Babaeva and Naidis, 2016b;Babaeva and Naidis, 2016a;Marode et al, 2016;Tardiveau et al, 2016;Tarasenko et al, 2020;Chen et al, 2020;Bourdon et al, 2020;Babaeva and Naidis, 2021;Zhu et al, 2021). Rather good agreement between experiments and simulations has been obtained on discharge characteristics such as the maximum discharge radius and ionization front velocity as reviewed in Naidis et al (2018); Babaeva and Naidis (2021) and on the time evolutions of the electric field on the symmetry axis as shown at very early times of discharge propagation in Brisset et al (2019) and during the whole discharge propagation in the gap in Bourdon et al (2020); Zhu et al (2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] It has been well validated that the evolution of a spark channel (and corresponding E/N value) can be well described by a volume‐averaged global model. [ 45 ]…”
Section: Resultsmentioning
confidence: 99%
“…[40] It has been well validated that the evolution of a spark channel (and corresponding E/N value) can be well described by a volume-averaged global model. [45] The second question is how to reproduce such specific E/N temporal profiles in real experiments? There is a gap between the voltage profile and the electric field temporal profile.…”
Section: Discussion: Implementation Of ML Predicted Solution In Real ...mentioning
confidence: 99%